The (ir)relevance of real wage rigidity for optimal monetary policy - Britta Kohlbrecher (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2019)
Real wage rigidity is known to create a substantial trade-off between inflation and employment stabilization for monetary policy in New Keynesian models with search frictions on the labor market. This paper shows that, quantitatively, this finding hinges very much on the assumption of constant returns to scale in production. With decreasing returns to scale, monetary policy with a single focus on inflation stabilization is close to optimal. The reason is twofold: Firms cushion the impact of rigid real wages on marginal costs by adjusting the marginal product of labor over the cycle. In addition, given employment fluctuations have a smaller effect on consumption volatility. Decreasing returns to scale thus remove the need for active monetary policy even if wages are rigid. Importantly, this contrasts with the implications of combining real wage rigidity and decreasing returns to scale for other policy instruments.
Keywords: E24; E32; E52; J64; 330; optimal monetary policy; Ramsey policy; search and matching; real wage rigidity